Design & prototype physical structure units for droplet manipulation in magnetic digital microfluidics - Ahmad Adnan Firdaus (2019)
This study explores the field of magnetic digital microfluidics and exploits the concept to create a modular-based prototype of physical assistive structures for droplet manipulation. Magnetic digital microfluidics has been an emerging research field of its own for around a decade. With the ability to integrate various laboratory concepts onto single chip, the potential for applications using this concept is limitless. The project will involve two processes: the design generation and the functional ability testing of the modular-based prototypes. These two processes will be conducted simultaneously so as to complement each other, achieving optimal results within a shorter time, as compared to conducting the processes one at a time. The first process of design generation involves the modelling of the assistive physical structures using SolidWorks. Drafting the models is necessary for better visualization and crucial to the design development. Once the design models have been examined, the drawings will be converted to .STL files to be printed out using 3D-printing machines such as Fused Deposition Modelling (FDM) and Stereolithography Apparatus (SLA). Once the assistive structures have been printed out, the functional ability testing of these prototypes can now proceed, determining the capabilities of performing the intended functions. Finally, this report will present the findings and discuss the possible reasons behind he results. Subsequently, the report will end with a conclusion regarding the results observed and recommendations regarding the possible future areas of study related to the progress of the project. As scheduled, the author had a weekly meeting with his superiors from the start of the year for updates and feedbacks on the progress of this project.